(untitled) (Journal of Hama University, 2025)
Introduction: The importance of the nursing practice work environment comes from its impact on many variables among nursing staff, such as: psychological reassurance, physical safety, performance level, job satisfaction, and the nurse’s behavior at work. Developing working conditions in hospitals has a positive impact on improving the quality of care provided, through By enhancing performance and raising the level of motivation among nursing staff, Aim: To assess the nursing practice work environment at Tishreen University Hospital in Lattakia from the perspective of the nursing staff, Research materials and methods: This research relied on a descriptive approach and a cross-sectional survey design on a sample that included 283 nurses from the nursing staff who were selected using the available sample method in the morning and evening shifts, in the internal medicine, surgery and intensive care departments using the PES-NWI scale according to Lake (2002). The study data was transcribed and statistically analyzed by the researcher using the Statistical Package for the Social Sciences (SPSS) program, version 25, Findings: The Findings showed that the nursing staff assesses the practice’s work environment as unfavorable (3.1), in all dimensions, respectively, except for the dimension of the collegial relationship with physicians, Conclusion: The prevailing characteristic of the practice work environment from the point of view of the nursing staff at Tishreen University Hospital is the good relationship between physicians and nurses, and the minimum is the adequacy of resources and equipment. Recommendations: Enhancing opportunities for nursing staff members to participate in hospital affairs, empowering nurses, providing fair opportunities for professional development, and conducting nursing workshops.